Studying the Probability of Using Groundwater in Baghdad City for Human, Animal, and Irrigation Use - Channo, Reem J. (Al-Khwarizmi Engineering Journal, 2012)
Groundwater is an important source of fresh water especially in countries having a decrease in or no surface water; therefore itis essential to assess the quality of groundwater and find the possibility of its use in different purposes (domestic; agricultural; animal; and other purposes). In this paper samples from 66 wells lying in different places in Baghdad city were used to determine 13 water parameters, to find the quality of groundwater and evaluate the possibility of using it for human, animal and irrigation by calculating WQI, SAR, RSC and Na% and TDS indicators. WQI results showed that the groundwater in all wells are not qualified for human use, while SAR and RSC indicated that most samples are suitable for irrigation use, and TDS showed that 74% of samples are suitable for animal use especially for sheep and meat-livestock animals.